TOP SECRET ROSIES. - Wolverton, Mark (American Heritage)
The article discusses the work of the Philadelphia Computing Section (PCS) of the University of Pennsylvania, a group of women who did mathematical work in support of the U.S. military during World War II. These women essentially acted as human computers who calculated trajectories and other figures to be used by advanced weapons systems such as bomber planes and howitzer guns. Many of these women were also involved in creating the first electronic computer.